Female and male student teacher’s motives in choosing teaching as a career - Repblicha Astriyadi (Jurnal Sinar Edukasi, 2024)
This quantitative study investigates the motives influencing male and female student teachers to pursue teaching careers at a public university in Jambi Province, Indonesia. Utilizing a survey design, the research examined altruistic, intrinsic, and extrinsic motivational factors among 217 first-year students from English (n=114) and Mathematics (n=103) education programs, comprising 172 females (79.3%) and 45 males (20.7%). A twelve-item Likert-scale questionnaire adapted from established international instruments was employed to measure three motivational categories: altruistic (social utility and desire to help society), intrinsic (job activity itself and interest in teaching), and extrinsic (material benefits and external rewards). Data were analyzed using descriptive statistics, including frequency distributions and percentage comparisons. Findings revealed that across all participants, the highest-rated motives were "I want to shape future of children" (61.8%) from altruistic factors, "It offers opportunities for my academic development" (66.4%) from intrinsic factors, and "Being a teacher offers good salary/better future" (57.1%) from extrinsic factors. Gender analysis showed that female participants were predominantly motivated by "I love to work with children" (61%), while male participants prioritized "I want to shape future of children" (73.3%). Program comparison indicated that English students emphasized altruistic motives, particularly shaping children's futures (74.6%), whereas Mathematics students highlighted intrinsic motivation for academic development (73.8%). The study addresses a significant research gap in Indonesian teacher education contexts and provides empirical evidence for policymakers and educational institutions to develop effective recruitment and retention strategies for committed, quality teachers in Indonesia's developing educational system.